IMPLEMENTASI PROGRAM PENGELOLAAN DAN PENATAAN HUTAN KOTA PATRIOT BINA BANGSA DI KOTA BEKASI - Hayumi Febyan Chealsiyana; Cucu Sugiarti; Haura Atthahara (EnviroScienteae, 2021)
The function of urban forest can reduce the impact of the greenhouse effect, while on a micro level, it is to eliminate the negative impact of urban development and economic development. The purpose of the existence of urban forests is to eliminate the imbalance of urban ecosystems as a result of economic development and population growth that tends to be green open space. Thus, urban forests can endanger or at least be able to maintain ecosystem balance, temperature changes, air pollution, air pollution, decreased ground air levels and the danger of flooding. Several objectives are based on the discipline of Government Science that uses Rippley and Franklin's program policy implementation model, including to understand and understand the level of censorship, at any time and to understand smooth and no problems in management and arrangement, and to see and understand the performance of the apparatus in management. and the arrangement of the Patriot Bina Bangsa City Forest. The research technique used in this research is literature study and field studies with observation, interviews, and documentation. This type of research is qualitative using descriptive analysis method with a theoretical basis to provide an overview of the research background and as material for the discussion of research results. Based on the results of research that applies the implementation theory of the Rippley and Franklin model, it shows that the implementation in the management of the Patriot Bina Bangsa City Forest has not been successful, and needs evaluation for the future.